Slow-release nitrogen fertiliser suitable for one-time fertilisation of spring maize in Northeast China - Xiaojie Feng; Xiumei Zhan; Xiaori Han; Kun Chen; Jing Peng; Xuexin Wang; Dongyao Shang (Plant, Soil and Environment, 2021)
Slow-release nitrogen fertiliser can potentially increase crop production and improve fertiliser nitrogen use efficiency. However, it is unclear that are suitable for different regions and crops in the northeast of China. Therefore, according to different soil and climate characteristics, we investigated the synchronised relationships between nitrogen slow release fertiliser and nitrogen maize requirements. Experiments were conducted at Shenyang Agricultural University, Liaoning province, Northeast China, from 2016 to 2017. Stabilised fertiliser treatments increased grain yield, nitrogen use efficiency and nitrogen accumulation at each maize growth stage. Grain yield increased by 2.32% and 11.33% (2016), and 1.55% and 7.87% (2017), respectively, when compared with the urea CK1 (233 kg N/ha) and CK2 (210 kg N/ha) treatments. Additionally, during the growth period of the stabilised fertiliser treatment, the stability of the synchronisation relationship between nitrogen absorption and absorption of spring maize was significantly higher than other treatments, and the effect was the best. Therefore, we conclude that the stabilised fertiliser is the most suitable option for promotion and application in spring maize in Northeast China.